Heat transfer performance of two-phase closed thermosyphon with oxidized CNT/water nanofluids - Heris, S.Z.; Fallahi, M.; Shanbedi, M.; Amiri, A. (Springer Verlag (Germany), 2016)
In this paper, the effects of different acids on the thermal performance of oxidized carbon nanotubes (CNT)/water nanofluids in a two-phase closed thermosyphon were studied. The structures morphology and functionalization degree were studied concurrently. The results indicated that strong oxidants increased dispersivity of CNT in the nanofluids. In other words, as the number of COOH groups increased in the nanofluids, an upward trend was also observed in the thermal efficiency of the thermosyphon.